Spillover effects in oligopolistic markets - Klaus Gugler; Florian Szücs (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
We estimate the spillovers on firm profitability and market shares in oligopolistic markets through the transition from an n to an n-1 player oligopoly after a merger in the industry. Competitors are identified via the European Commission s market investigations and our methodology allows us to disentangle the spillover due to the change in market structure from the merger effect. We obtain results consistent with the predictions of standard oligopoly models: non-merging rivals expand their output and increase their profits, while merging firms barely break even. The size of the effect is larger in industries with fewer oligopolists and higher initial profits.
Keywords: L13; L40; G34; 330